Phytoplasmas: Genomes, Plant Hosts and Vectors - Weintraub, Phyllis G (CABI, 2014)
In this book we have tried to examine all aspects related to phytoplasmas, their plant hosts and insect vectors and so present the reader with the state of the art in a logical, coherent fashion. Since phytoplasmas are fastidious, diagnostic methods and quantification assume greater importance because one is limited in the scope of available techniques. For example, serological methods are very limited with an organism that cannot be artificially cultured. The opening chapter is followed by chapters on sequencing and functional genomics, which relies heavily on comparing phytoplasma genomics with that of other known bacteria.